2009
DOI: 10.1371/journal.pgen.1000328
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis CULLIN3 Genes Regulate Primary Root Growth and Patterning by Ethylene-Dependent and -Independent Mechanisms

Abstract: CULLIN3 (CUL3) together with BTB-domain proteins form a class of Cullin-RING ubiquitin ligases (called CRL3s) that control the rapid and selective degradation of important regulatory proteins in all eukaryotes. Here, we report that in the model plant Arabidopsis thaliana, CUL3 regulates plant growth and development, not only during embryogenesis but also at post-embryonic stages. First, we show that CUL3 modulates the emission of ethylene, a gaseous plant hormone that is an important growth regulator. A CUL3 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(65 citation statements)
references
References 60 publications
3
61
0
1
Order By: Relevance
“…We believe that the localized cellular sites of ethylene production, rather than the absolute amount of ethylene produced by an intact seedling or plant, determine the developmental response and outcome. Even though it is volatile and therefore highly diffusible, ethylene can induce different local responses depending on its site(s) of production and/or perception (Stepanova et al 2008;Thomann et al 2009). This agrees with the findings that the ACS genes have distinct patterns of expression during Arabidopsis development .…”
Section: Discussionmentioning
confidence: 99%
“…We believe that the localized cellular sites of ethylene production, rather than the absolute amount of ethylene produced by an intact seedling or plant, determine the developmental response and outcome. Even though it is volatile and therefore highly diffusible, ethylene can induce different local responses depending on its site(s) of production and/or perception (Stepanova et al 2008;Thomann et al 2009). This agrees with the findings that the ACS genes have distinct patterns of expression during Arabidopsis development .…”
Section: Discussionmentioning
confidence: 99%
“…The plates were kept at 4°C in the dark for 3 to 4 days to stratify and then exposed to 3 h of white light at room temperature before being placed in the dark for 21 h. The plates were incubated at 21°C for an additional 3 days in the dark or light as indicated. Arabidopsis thaliana wild type and various mutants (pif1, cop1-4, cop1-6, spa1, spa2, spa12, spa123, spa124, spaQ, cul1-6, cul3a, cul3b, cul3ab, cul4-1 and cul4cs) in the Col-0 background were used 6,32,[40][41][42][43][44][45][46][47][48] . For generation of different spaQpif1 mutant, pif1 and spaQ were crossed to obtain the F1 seeds.…”
Section: T a P -P I F 1 / C O P 1 -H A T A P -P I F 1 T A P -P I F 1 mentioning
confidence: 99%
“…11 Disruption of ETO1/EOLs, CUL3, or the domain in the type-2 ACS proteins that ETO1/EOLs interact with reduces the turnover of these ACS proteins, leading to an increase in the biosynthesis of ethylene. 7,[10][11][12][13] Despite their importance, relatively little is known regarding how E3 ligases themselves are regulated in plants. Recently, we have shown that the 14-3-3 proteins bind to both the ACS proteins and to the ETO1/EOL E3 ligases to regulate their stability.…”
mentioning
confidence: 99%